2014
DOI: 10.1021/ef500525v
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Centimeter-Scale Woody Biomass Particles: Kinetic Modeling and Experimental Validation

Abstract: Pyrolysis of centimeter-scale wood particles is of practical interest and provides a sensitive test of pyrolysis models, especially their thermochemistry. In this paper we present an updated comprehensive pyrolysis model including chemical reactions and transport of heat and species, implemented independently in two different software environments. Results of the model are compared to experimental results of three independent sets of centimeter-scale experiments. Temperatures, mass losses, and rate of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(179 citation statements)
references
References 34 publications
9
170
0
Order By: Relevance
“…When Bi <1, external heat transfer is the pyrolysis controlling parameter. In the case of Py <1 and Bi >1, thermal gradients exist in biomass particles, and therefore, reactions occur only in the thin region near the particle surface (Corbetta et al, ; Mettler, Paulsen, Vlachos, & Dauenhauer, ; Paulsen et al, ). When Pe >1 the rate of diffusion of bio‐oil and gases through the reacting biomass particle is slower than the convective mass transfer.…”
Section: Transport Effectsmentioning
confidence: 99%
“…When Bi <1, external heat transfer is the pyrolysis controlling parameter. In the case of Py <1 and Bi >1, thermal gradients exist in biomass particles, and therefore, reactions occur only in the thin region near the particle surface (Corbetta et al, ; Mettler, Paulsen, Vlachos, & Dauenhauer, ; Paulsen et al, ). When Pe >1 the rate of diffusion of bio‐oil and gases through the reacting biomass particle is slower than the convective mass transfer.…”
Section: Transport Effectsmentioning
confidence: 99%
“…It is based on the scheme developed by Ranzi et al [12] for pyrolysis of small ash free biomass particles (i.e., primary pyrolysis) called from now on original scheme. A recent update of this scheme, which has not been employed in this work, was presented by Corbetta et al [14]. Biomass consists of cellulose, hemicellulose and 3 types of lignin which independently decompose and the volatiles are represented by 20 species, including main permanent gases and condensable species.…”
Section: Kinetic Schemementioning
confidence: 99%
“…We can conclude that mass loss of lignocellulosic biomass torrefaction can be also predicted with this detailed kinetic scheme, although certain deviations are present at very low temperatures. Corbetta et al [14] have already shown that the Ranzi scheme is able to predict mass loss evolution of cellulose, hemicellulose and lignin under torrefaction conditions.…”
Section: Mass Loss Evolutionmentioning
confidence: 99%
“…The segregation of thick wood samples such as chips or pellets in sand beds has been less studied compared to pyrolysis/gasification/ combustion kinetics [4][5][6][7][8][9][10][11][12][13][14][15] or fluidized bed hydrodynamics [1,3,[16][17][18][19][20][21]. Some studies conducted on solid mixing in fluidized beds have focused on particles with the same density but different shapes or diameters [22][23][24] or particles with the same shape but different densities [22].…”
Section: Introductionmentioning
confidence: 99%